The Friendship’s Values in Teenlit Dealova, Rahasia Bintang and Tetralogy “Kosan Soda” by Dyan Nuranindya - Wuryani, Titi; Nuryatin, Agus (Pascasarjana Universitas Negeri Semarang, 2019)
The novel by Dyan Nuranindya namely Dealova, Rahasia Bintang and Tetralogy